IgG sialylation occurs in B cells pre antibody secretion - Werner, Anja; Hanić, Maja; Zaitseva, Olga O.; Lauc, Gordan; Lux, Anja; Nitschke, Lars; Nimmerjahn, Falk (Frontiers in Immunology, 2024)
Sialic acids as terminal sugar residues on cell surface or secreted proteins have many functional roles. Especially the presence or absence of α2,6-linked sialic acid residues at the immunoglobulin G (IgG)-Fc-fragment can switch IgG effector functions from pro-to anti-inflammatory activity. IgG glycosylation is considered to take place inside the plasma blast/plasma cell while the molecule travels through the endoplasmic reticulum and Golgi apparatus before being secreted. However, more recent studies have suggested that IgG sialylation may occur predominantly post antibody secretion. To what extent this extracellular IgG sialylation process contributes to overall IgG sialylation remains unclear, however. By generating bone marrow chimeric mice with a B cell specific deletion of ST6Gal1, the key enzyme required for IgG sialylation, we now show that sialylation of the IgG Fc-fragment exclusively occurs within B cells pre IgG secretion. We further demonstrate that B cells expressing ST6Gal1 have a developmental advantage over B cells lacking ST6Gal1 expression and thus dominate the plasma cell pool and the resulting serum IgG population in mouse models in which both, ST6Gal1 sufficient and deficient B cells are present.